Contested Commensuration: The case of a valuation instrument for historical buildings - Van der Schoor, Tineke C.; Peine, Alexander; Van Lente, Harro (Valuation studies, 2024)
Environmental values are becoming increasingly important in restoration of historical buildings, while energy interventions can seriously damage historical qualities. Cultural-historical values and environmental values are often considered difficult to commensurate, with energy engineers and heritage experts adhering to widely differing values and relating to different discourses. Valuation instruments are devised to deal with such value conflicts in restoration projects. In this article we study what such instruments perform in the case of assessing historical buildings. We ask how these instruments work, and how they afford, support and guide valuation processes? Furthermore, we enquire what is achieved and what is lost in the reconciliation of values. Theoretically, we start from the notion of commensuration, which allows comparison of values through a shared metric. Empirically, this research note examines the history and use of DuMo, an instrument that aims to reconcile cultural – historical and environmental values and provides a range of sustainable restoration strategies. We find that DuMo indeed performs commensuration of these conflicting values, but also keeps intact the epistemic authority of the two professions. Our claim thus is that valuation instruments can successfully perform commensuration while at the same being contested by involved professionals.